ENHANCING CREATIVE AND CRITICAL THINKING THROUGH PROBLEM-BASED LEARNING WITH CULTURALLY RICH INDONESIAN CONTENT - Pudma Febby Mandalika, Wayan; Susanti, Maria Melani Ika; Prasetya, Andreas Erwin (Jurnal Pendidikan Ilmu Sosial, 2024)
This research aims to improve creative and critical thinking skills in culturally rich Indonesian material by implementing the Problem Based Learning (PBL) learning model for grade 4 elementary school students. This research method is classroom action research. Data collection techniques in this research are non-test techniques and test techniques. Non-test techniques include observation, questionnaires and interviews. All of the students in the class were the subjects of this classroom action research IV D of SD Negeri Pujokusuman 01, totaling 28 students, consisting of 14 female students and 14 male students. The results of observations and interviews found that after the treatment was carried out, students were able to find many problems and solutions from learning sources and in their own sentences. The results of the questionnaire data analysis showed that the ability to think creatively and critically had increased, from 69.7% in the pre-cycle, 73.4% in the first cycle to 83% in the second cycle. The results of data analysis using tests showed that the ability to think creatively and critically had increased, from 68% in the precycle, 77% in the first cycle to 84.5% in the second cycle. Based on this research, it can be concluded that the implementation of the Problem Based Learning (PBL) learning model can improve the creative and critical thinking abilities of grade 4 students at SD Negeri Pujokusuman 01 on Indonesia Kaya Budaya in IPAS culture.